Safety of Metoclopramide in Traumatic Brain Injury Patients - Jaadi, Said Al; Al-Kindi, Yahya; Al-Saadi, Tariq (Indian Journal of Neurotrauma, 2020)
Introduction Traumatic brain injuries (TBIs) occur due to severe head assault to a hard object, with headache and vomiting being amongst the most common presenting symptoms. Metoclopramide is an old antiemetic agent that has been used widely for nausea and vomiting in TBI patients.Aim A systematic review of the literature to investigate the safety of metoclopramide in treating TBI patients.Methods A literature review was conducted in six databases, where we determined the pertinence of a study to the inclusion criteria by assessing the title, keywords, and abstracts. Five studies were found to be relevant. Data were extracted using multiple variables that were formulated incongruent with the study aim and then further analyzed.Results The collective sample size was 93 patients with an average of age 38.5 years. As much as 51.6% were male and 48.6% were females. Most patients received 10 mg metoclopramide IV with a percentage of 77.4%, while only 22.5% received 20 mg IV metoclopramide. Seventy-one patients received metoclopramide alone and 22 received combination therapy. Headache was the most common reported side effect (46.2%), followed by anxiety and drowsiness with (39.7%) and (27.9%), respectively. Fatigue was reported in 24.7%, while dystonia was the least common and developed in only 5.3% of patients.Conclusion Metoclopramide is a common medication used to treat TBI patients in the emergency department. However, the review demonstrated that the central nervous system (CNS) side effect is excepted. Treatments with lower CNS side effects may be better options.
Keywords: traumatic head injury; metoclopramide; safety; side effect; headache; vomiting